Coyote and the Colville - Yanan, Eileen (St. Mary's Mission, 1971)
This book is a general introduction to the history of the land and peoples of the Colville Indian Reservation. The first [part] deals with the history of the area that was and is the Colville Indian Reservation. The second section of the book provides a number of Indian legends, popularly known as Coyote stories--Forward, p. 5.